Resection of Navigated Transcranial Magnetic Stimulation-Positive Prerolandic Motor Areas Causes Permanent Impairment of Motor Function. Issue 1 (24th February 2017) - Moser, Tobias; Bulubas, Lucia; Sabih, Jamil; Conway, Neal; Wildschutz, Noémie; Sollmann, Nico; Meyer, Bernhard; Ringel, Florian; Krieg, Sandro M.
Abstract: BACKGROUND: Navigated transcranial magnetic stimulation (nTMS) helps to determine the distribution of motor eloquent areas prior to brain surgery. Yet, the eloquence of primary motor areas frontal to the precentral gyrus identified via nTMS is unclear. OBJECTIVE: To investigate the resection of nTMS-positive prerolandic motor areas and its correlation with postsurgical impairment of motor function. METHODS: Forty-three patients with rolandic or prerolandic gliomas (WHO grade I-IV) underwent nTMS prior to surgery. Only patients without ischemia within the motor system in postoperative MRI diffusion sequences were enrolled. Based on the 3-dimensional fusion of preoperative nTMS motor mapping data with postsurgical MRI scans, we identified nTMS points that were resected in the infiltration zone of the tumor. We then classified the resected points according to the localization and latency of their motor evoked potentials. Surgery-related paresis was graded as transient (≤6 weeks) or permanent (>6 weeks). RESULTS: Out of 43, 31 patients (72%) showed nTMS-positive motor points in the prerolandic gyri. In general, 13 out of 43 patients (30%) underwent resection of nTMS points. Ten out of these patients showed postoperative paresis. There were 2 (15%) patients with a transient and 8 (62%) with a permanent surgery-related paresis. In 3 cases (23%), motor function remained unimpaired. CONCLUSION: After resection of nTMS-positive motor points, 62% of patients suffered from a new permanent paresis. Thus, even though they are located in the superior or middle frontal gyrus, these cortical areas must undergo intraoperative mapping.